Pengaruh Citra Merek, Kualitas Pelayanan dan Kesadaran Merek Terhadap Kepuasan Konsumen di Hits Chicken Kediri - Rustandi, Lucky Rama; Muttaqien, Zaenul; Jauhari, Ahmad (UNIVERSITAS MARITIM AMNI SEMARANG, 2025)
This study aims to analyze the influence of brand image, service quality, and brand awareness on customer satisfaction at Hits Chicken Kediri. The research employed a quantitative approach with an associative design. The population consisted of all Hits Chicken customers, with 117 respondents selected using incidental sampling. Data were collected through a five-point Likert scale questionnaire and analyzed using multiple linear regression with SPSS version 25.0. The results indicate that brand image has a positive and significant effect on customer satisfaction. Service quality also shows a significant influence, as fast, friendly, and consistent service improves customer satisfaction. Furthermore, brand awareness significantly affects satisfaction since customers tend to choose easily recognizable brands. The simultaneous test confirms that the three independent variables significantly influence customer satisfaction, with a coefficient of determination (R²) of 44.9%. These findings highlight the importance of integrated strategies in strengthening brand image, improving service quality, and building brand awareness to enhance customer satisfaction.